Analysis of Basic Principles and Governance in Education - Lenni Sri Rejeki Pasaribu; Elfrianto Elfrianto; Rosmiaty Rosmiaty; Nurul Widyawati (Edumaspul: Jurnal Pendidikan, 2022)
This research seeks to analyze or examine the basic principles and governance of education, education that has good management is of course a quality institution and has very good results as well. The research method used is in the form of a literature review analysis by looking for reading sources in the form of books, journals, or certain magazines and news. From the results of the study, it was found that educational governance is a very important factor in improving the quality of education, in managing an educational institution it is necessary to have principles in its management. Some of these principles should be a benchmark or the basis for determining the quality of good education.